The Need to Develop an Effective Business Activity Management Strategy in the Construction Network (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The authors address the changes being made by entrepreneurs today with their suggestions and ideas to find a solution to the current problem. The article discusses the necessity of developing an effective management strategy for entrepreneurship in the construction sector and its solutions, as well as what can be achieved by developing entrepreneurship in the construction sector and what changes can be made in entrepreneurship if a management strategy is created.